Determination of salivary concentrations of leptin and adiponectin, ability to reduce ferric ions and total antioxidant capacity of saliva in patients with severe early childhood caries - Petrović, Bojan; Stilinović, Nebojsa; Tomas, Ana; Kojić, Sanja; Stojanović, Goran M. (Frontiers in Pediatrics, 2022)
Introduction: One of the most common oral diseases affecting children is early childhood caries (ECC). The link between oxidative stress and ECC has been proven in numerous clinical studies. Technical and biological variability were so high in most of the studies that none of the markers have yet been proven suitable for routine clinical use. This study aimed to evaluate the antioxidant status and the levels of leptin and adiponectin in saliva of children with severe early childhood caries (S-ECC). Methods: Morning unstimulated saliva samples were collected from children (n=40, 0-6 years old) for the evaluation of oxidative stress which were measured by total antioxidant capacity (TAC), and by the ferric reducing antioxidant power (FRAP) assays, as well as to assess the salivary levels of leptin and adiponectin. FRAP, TAC, leptin and adiponectin concentrations were evaluated in S-ECC group (n=31) and caries free group CF (n=9). Results: Median salivary leptin and adiponectin levels were 5.59 pg/mL and 24.86 ng/mL, respectively. Significantly lower leptin levels were observed in saliva of caries free children than in the S-ECC group. The results indicated that the TAC and FRAP of saliva had similar values in children with S-ECC and caries free children. TAC and FRAP values also remained stable with the age of the children, without significant differences with respect to sex. Conclusions: The increased concentrations of leptin in saliva of children with S-ECC suggests that leptin may play a role in inflammatory and immune responses in the development of early childhood caries.